Correction to: Mechanically Induced Periprosthetic Osteolysis: A Systematic Review. Issue 1 (February 2020) - McArthur, Benjamin A.; Scully, Ryan; Ross, F. Patrick; Bostrom, Mathias P. G.; Fahlgren, Anna
Figure 2 and its caption were inadvertently omitted from the original article. The figure and caption are given below.